Hubungan Pola Makan Dan Riwayat Asi Eksklusif Dengan Angka Kejadian Stunting Pada Anak Balita Di Kelurahan Duren Mekar Bojongsari Kota Depok Tahun 2023 - Ibrahim Sahasika; Hari Ghanesia Istiani; Eka Rokhmiati (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Background: Stunting is a form of malnutrition which is characterized by indicators of height according to age. The TB/U indicator provides an indication of chronic nutritional problems as a result of a long-standing condition. Objective: in this research is to determine the relationship between eating patterns and history of exclusive breastfeeding with the incidence of stunting in children under five in Duren Mekar Bojongsari Village in 2023. Method: This research uses a descriptive correlation research design with a cross sectional approach. Correlation design is research that connects variables. one to another, and approaches. The number of samples that will be used in this research is 50 children under five. Data was collected using a CFQ (Child Feeding Questionnaire) questionnaire and toddlers' height was measured using a microtoise and converted into standardized values. Data analysis was carried out in percentage form and used the chi-square statistical test. Research Results: It was found that the sig value of diet was 0.009 < 0.05 and the sig value of Exclusive Breastfeeding History was 0.013 < 0.05. So Ha is accepted, meaning that there is a relationship between diet and history of exclusive breastfeeding with the incidence of stunting in children under five in Duren Mekar Bojongsari Village, Depok City in 2023. Based on the correlation coefficient of diet with the incidence of stunting of 0.023 and the correlation coefficient of history of exclusive breastfeeding with the incidence of stunting of 0.023. 0.028. This means that the level of correlation between diet and history of exclusive breastfeeding with the incidence of stunting is strong.